2016
DOI: 10.1021/jacs.6b04064
|View full text |Cite
|
Sign up to set email alerts
|

Robust Cross-Linked Stereocomplexes and C60 Inclusion Complexes of Vinyl-Functionalized Stereoregular Polymers Derived from Chemo/Stereoselective Coordination Polymerization

Abstract: ABSTRACT:The successful synthesis of highly syndiotactic polar vinyl polymers bearing the reactive pendant vinyl group on each repeat unit, which is enabled by perfectly chemoselective and highly syndiospecific coordination polymerization of divinyl polar monomers developed through this work, has allowed the construction of robust crosslinked supramolecular stereocomplexes and C 60 inclusion complexes. The metal-mediated coordination polymerization of three representative polar divinyl monomers, including viny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 103 publications
(51 reference statements)
4
44
0
Order By: Relevance
“…190 A more impressive example involved the inclusion of C 60 fullerene within a cross-linked methacrylate complex. 343 Interestingly, the inclusion complex exhibited a novel transition (T m inclusion complex = 205 °C) that was not present in the fullerene, homopolymer, or the annealed blend.…”
Section: Pmmamentioning
confidence: 98%
“…190 A more impressive example involved the inclusion of C 60 fullerene within a cross-linked methacrylate complex. 343 Interestingly, the inclusion complex exhibited a novel transition (T m inclusion complex = 205 °C) that was not present in the fullerene, homopolymer, or the annealed blend.…”
Section: Pmmamentioning
confidence: 98%
“…For instance, Desroches et al previously reported the successful quantitative thiol‐ene coupling of mercaptoethanol on OLA unsaturations (Desroches et al, ). Alternatively to the modification of monomers, this reaction can also be employed in a postpolymerization functionalization approach, if the polymer still contains vinyl groups after polymerization (Hoyle and Bowman, ; Vidal et al, ; Vidal et al, ). Then, thiol‐ene coupling of OLA with alkyl thiols containing long aliphatic chains could yield suitable highly hydrophobic monomers for providing high performant polymer‐based VII for MPO.…”
Section: Introductionmentioning
confidence: 99%
“…Limited catalyst systems have been developed for the chemoselective polymerization of polar divinyl monomers under mild conditions [ 15 ]. Chen’s group recently reported an elegant example of the chemoselective polymerization of polar divinyl monomers by using chiral ansa-zirconocene enolates, affording a highly stereotactic polymer [ 17 , 18 ]. The same group achieved complete chemoselectivity in the polymerization of multivinyl-functionalized γ -butyrolactones by utilizing N -heterocyclic carbene (NHC) catalysts [ 19 ].…”
Section: Introductionmentioning
confidence: 99%